Properties of Contra (1,2)*-Sg-Continuous Maps - G.Ramkumar, M. Jegadeesan (Mathematical Statistician and Engineering Applications, 2021)
Ravi and Lellis Thivagar introduced a bitopological space in the year 2006. Many modern topologists have worked in the field of bitopological spaces using the idea of Ravi and Thivagar. In this paper, we study the bitopological properties of the new class of contra-(1,2)*-sg-continuous maps